Autofluorescence lifetime imaging classifies human B and NK cell activation state - Schmitz, Rebecca L.; Riendeau, Jeremiah M.; Tweed, Kelsey E.; Rehani, Peter; Samimi, Kayvan; Pham, Dan L.; Jones, Isabel; Maly, Elizabeth M.; Contreras Guzman, Emmanuel; Forsberg, Matthew H.; Shahi, Ankita; Hockerman, Lucia; et al. (Frontiers in Bioengineering and Biotechnology, 2025)
New non-destructive tools with single-cell resolution are needed to reliably assess B cell and NK cell function for applications including adoptive cell therapy and immune profiling. Optical metabolic imaging (OMI) is a label-free method that measures the autofluorescence intensity and lifetime of the metabolic cofactors NAD(P)H and FAD to quantify metabolism at a single-cell level. Here, we demonstrate that OMI can resolve metabolic changes between primary human quiescent and IL-4/anti-CD40 activated B cells and between quiescent and IL-12/IL-15/IL-18 activated NK cells. We found that stimulated B and NK cells had an increased proportion of free compared to protein-bound NAD(P)H, a reduced redox state, and produced more lactate compared to control cells. The NAD(P)H mean fluorescence lifetime decreased in the stimulated B and NK cells compared to control cells. Random forest models classified B cells and NK cells according to activation state (CD69+) based on OMI variables with an accuracy of 93%. Our results show that autofluorescence lifetime imaging can accurately assess B and NK cell activation in a label-free, non-destructive manner.